Ethiopia’s history and historiography in perspective: a post-modernist critique and policy implications for national cohesion - Solomon Gebre Weldeananiya; Kenneth Omeje (Cogent Social Sciences)
Ethiopia’s history is deeply rooted and intertwined in the country’s polarized politics, leading to a complex and contested historical landscape and interpretation. This has resulted in rival historiographical perspectives and contradictions between Ethio-nationalist and ethno nationalist schools. The positivistic meta-narrative of Ethiopian historiography held by the Ethio nationalists argues that the postmodernist approach espoused by the ethno nationalists threatens the grand narrative of Ethiopian history and challenges the objectivity of history as a scientific discipline. This article aims to expose and criticize these fallacies and contradictions in Ethiopianist historical metanarratives. A qualitative explorative case study design was used to gather data from primary and secondary sources. The primary sources were interviews with purposely-selected eight key informants representing varying historical perspectives. The secondary sources include content analysis from documents, established literature, and social media. Content and thematic analyses were used for data interpretation and generalization. The study found that foreign writers’ perspectives, Ethio-nationalist perspectives, ethno-nationalist perspectives, and successive Ethiopian regimes’ historiographical perspectives have contributed to Ethiopia’s historiographical contradictions. This has entangled the historical debate with national-level political debate, negatively influencing national reconciliation and cohesion. The article recommends policy implications to enhance national cohesion through historical deconstruction, reinterpretation, and inclusivity of marginalized voices through new historicism.